The Effects of Using Snake and Ladder Media towards Elementary School Students’ Learning Outcomes - Yuli Mulyawati; Tustiyana Windiyani (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2020)
The purpose of this study was to determine the effect of using snake and ladder learning media towards students’ learning outcomes. This study used an experimental research method with a one-group pretest-posttest design. The research was conducted 34 fourth grade students from SDN Katulampa 1 Bogor in odd semester of 2020/2021 academic year. The analysis technique used is the analysis prerequisite test which includes the normality and homogeneity test. The research hypothess is carried out using the t-test. The results of experiment 1 showed that the scores of students’ learning outcomes increased from an average pretest score of 50.00 to 80.00 of posttests with N-Gain 60.00. While, the experiment 2 with the effect of using snake and ladder learning media resulted in an average pretest score of 53.43, posttest of 85.29, and N-Gain 68. Based on the results of the research, it can be concluded that there is an effect of the use of snake and ladder learning media towards elementary school students’ learning outcomes.